Optimization of Equivalent Source Configuration for an Independent-Equivalent Source Method in Half-Space Sound Field - Wen-Qian Jing; Huawei Wu; Jin-Quan Nie (Shock and Vibration)
In the situation that vibrating objects are located above a reflecting plane, an independent-equivalent source method (I-ESM) regards the reflections due to the plane as being radiated by equivalent sources placed under the plane and then the half-space sound field is reconstructed by matching the measured pressure with the equivalent sources distributed within the vibrating object and those substituting for reflections. But, this method heavily depends on the equivalent source configuration and may obtain bad reconstruction results if the equivalent sources are arranged incorrectly. This paper deals with the optimization of the equivalent source configuration to ensure I-ESM always perform well. Through numerical simulations and experiments, the influence of equivalent source configurations on the reconstruction accuracy was studied and optimal configurations were acquired and confirmed.